2018
DOI: 10.1115/1.4042076
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Twin for Grinding Wheel: An Information Sharing Platform for Sustainable Grinding Process

Abstract: Emerging re-industrialization demands the fusion of the physical and the digital world for the development of sustainable manufacturing processes. Sustainability in manufacturing aims at improving the resource productivity by identifying the environmental challenges as opportunities. In the present era of the fourth industrial revolution or digital manufacturing, manufacturers strive to gain value through every bit of data collection throughout the product lifecycle. Integration of the collected information as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Kannan and Arunachalam present a DT approach for a grinding wheel as a product-integrated and web-based knowledge sharing platform that integrates data collected in each phase of the grinding wheel's life time from the manufacturing to the conditioning phase. 25 Within the analysis, a case study with a special focus on productivity and efficiency was conducted resulting in a 14.4% energy and resource efficiency increase. While the publication clearly addresses aspects of sustainability, it leaves a number of questions unanswered.…”
Section: State Of Research and Standardizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kannan and Arunachalam present a DT approach for a grinding wheel as a product-integrated and web-based knowledge sharing platform that integrates data collected in each phase of the grinding wheel's life time from the manufacturing to the conditioning phase. 25 Within the analysis, a case study with a special focus on productivity and efficiency was conducted resulting in a 14.4% energy and resource efficiency increase. While the publication clearly addresses aspects of sustainability, it leaves a number of questions unanswered.…”
Section: State Of Research and Standardizationmentioning
confidence: 99%
“…Consequently, a number of recent publications present analysis and use cases that primarily link existing methods and thought patterns that are commonly associated with sustainability to the DT concept and outline technical challenges of a microeconomic implementation. Recent examples of these bottom-up approaches include a DT-based life cycle assessment (LCA) framework, [22] the conceptual basics of a DT concept for sustainability evaluation of railway station buildings, [23] an implementation model applicable in the context of asset life cycle management, [24] a method for DT-driven product design [25] as well as a DT-driven green material optimal selection model. [26] He and Bai present a substantial review of bottom-up-approaches related to DT-driven sustainable intelligent manufacturing and summarize their findings in a specific framework.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of machining, the digital twin of the grinding wheel is created in [12], and a web service channel enabled by the Internet of Things (IoT) is established. This could help to reduce the energy and manufacturing resources' consumption by 14.4%.…”
Section: B Digital Twin Contribution To Sustainabilitymentioning
confidence: 99%
“…Analysis of the state-of-the-art and of the needs of the current grinding industry showed that DT technology could be a very powerful tool to analyze, design and optimize industrial grinding processes [12]. In [61], the authors made the first attempt to use a DT applied to the grinding process, which focused on minimizing the environmental impact of the process by analyzing the wheel dressing cycles. However, in this work there is not concern for critical issues such as wheel wear, occurrence of part damage because of grinding burns, etc.…”
Section: Several Attempts Have Been Made To Analyze the Wear Of New Tmentioning
confidence: 99%